Diagnosis and treatment of intermuscular venous malformations: A retrospective study in one center. (July 2020) - Xu, Mengnan; Wang, Min; Cheng, Yenwen; Ni, Xiaodong; Xu, Yuan; Wang, Qian; Yuan, Siming
Objectives: Intermuscular venous malformations are common vascular malformation, do not have typical symptoms, and are difficult to diagnose. This article is a retrospective analysis of the diagnostic and therapeutic measures of intermuscular venous malformations. Methods: From January 2013 to June 2018, 21 patients were included in this study. The clinical presentations, managements, and follow-up results were retrospectively analyzed. The indications and potential risks of different treatments were summarized. Results: The complaints of patients with intermuscular venous malformations included local pain, swelling, discomfort, or aggravation after activity. Ultrasound, phlebography, magnetic resonance imaging, percutaneous sinus angiography, and three-dimensional computed tomography imaging were performed. The patients received surgical excision, sclerotherapy, or the combinational therapy of intralesional copper wires retention and ethanol injection and were followed for six months to five years. All patients' symptoms were relieved largely. The lesions evaluated by magnetic resonance imaging decreased apparently or disappeared. Conclusions: Imaging examinations are necessary in the diagnosis of intermuscular venous malformations and can guide the choice of treatment. Individualized treatment for intermuscular venous malformations should be made to achieve good effect and avoid adverse effects.